What's in Your Dataset? Measuring Engagement in HIV Care Using Routinely Administered Items with a Population Disproportionately Burdened by HIV. - Vincent, Wilson; Siconolfi, Daniel E.; Pollack, Lance; Campbell, Chadwick K.; Kegeles, Susan M.; Storholm, Erik D. (AIDS & Behavior, 2024)
We evaluated the psychometric properties of a measure consisting of items that assess current HIV care continuum engagement based on established definitions in the United States. At baseline, participants in this longitudinal study, which included three time points from 2015 to 2020, were 331 young Black sexual minority men ages 18–29 living with HIV in the southern United States residing in two large southern cities. Self-report items reflected four aspects of HIV care continuum engagement as binary variables: seeing a healthcare provider for HIV care, being on antiretroviral treatment, being retained in HIV care, and being virally suppressed. Of these, the following three variables loaded onto a single factor in exploratory factor analysis: being on antiretroviral treatment, being retained in HIV care, and being virally suppressed. A one-dimensional factor structure was confirmed using confirmatory factor analyses at separate time points. Additionally, the three items collectively showed measurement invariance by age, education level, employment status, and income level. The three-item measure also showed reliability based on coefficient omega and convergent validity in its associations with indicators of socioeconomic distress, depression, resilience, and healthcare empowerment. In sum, the items performed well as a single scale. The study demonstrated the potential psychometric strength of simple, feasible, commonly administered items assessing engagement in the HIV care continuum.